Antioxidant potential of edible coatings incorporated with unfermented and fermented noni residue extracts (Research, Society and Development, 2021)
The present work aimed to elaborate edible coatings based on chitosan and cassava starch incorporated with bioactive extracts obtained from unfermented and fermented noni residue flour. Initially, noni peel and seed flours were prepared and a mixture of these (NPSF) and noni peel flour (NPF) were used. The flours with initial moisture adjusted to 50 and 70% were submitted to solid state fermentation using the fungus Aspergillus niger. At each time of fermentation, different extracts were obtained in organic solvents (distilled water, 40% ethanol, 80% ethanol and 40% methanol) and evaluated for total phenolic and total flavonoid contents. The extracts from fermented flours with the highest content of total phenolic compounds were obtained in 40% methanol after 24h of FCSN fermentation and in 40% ethanol after 96h of FCN fermentation, these being selected for incorporation in edible coatings. In the next step, coatings containing 1% of cassava starch and varied percentages of chitosan (1 or 2%) and extracts of fermented and unfermented flours (5 or 10%) were prepared. The coatings containing fermented FCSN and FCN showed greater antioxidant activity in vitro by ABTS, DPPH and FRAP methods. Thus, it was showed that the extracts obtained from fermented flours were effective in increasing the antioxidant potential of edible coatings, which may be applied in future work in food preservation.